The Negotiation of Zainichi Identity and Resistance to Japanese Domination in Kazuki Kaneshiro Literary Text - Wawat Rahwati; Budi Mulyadi; Feri Purwadi (Universitas Diponegoro, 2020)
This study discusses the identity negotiation and resistance of the Zainichi minority to Japanese domination as the majority group in the literary text by Kazuki Kaneshiro. Zainichi is Korean people who came and have settled in Japan before and during World War II. As a minority group in Japan, Zainichi often faces discrimination from Japanese people due to his identity. Issues regarding the issue of Zainichi's identity are a dominant theme raised in the literary work of Zainchi (Zainichi bungaku). One of the authors of Zainichi's literary works is Kazuki Kaneshiro who wrote a novel entitled Go in 2007. Go novel as a literary text of Zainichi will be used as research data to reveal how Zainichi's identity negotiations are articulated by Zainichi characters and how their resistance against Japanese domination as the majority community group. By using postcolonial studies and analyses the structure of the narrative text, this research can reveal the forms of identity negotiation and resistances dis-course represented by Zainichi characters. Identity negotiation is seen through using Japanese name by Zainichi characters while interacting with the Japanese and changing the nationality from Korean to Japanese. Meanwhile, physical violence, mimicry (imitation), a mockery of Japanese behaviours, and maintaining their identity and Korean culture as resistances to counter the Japanese domination in the novel Go.